A condição ornamental: as origens e os fundamentos do ornamento arquitetural contemporâneo - Diogo Ribeiro Carvalho (2016)
The thesis deals with a problem of aesthetics in architecture, therefore, a problem of sensation and perception between the perceiver and what is perceived. The provision for this endeavour arises from the interest and a number of questions about one of the most exciting and radical architectural manifestations that has been developed in recent years; one that reinstalls the body in space and which has been categorized as exuberant and excessive. The experimental design and teaching productions of Marcos Cruz, Marjan Colletti and Hernan Diaz Alonso is an example. Although different in their approaches, one can observe three conditions that support their practices: (1) the body as founder of architecture; (2) the return of ornament and the figural; (3) poetics as relational element. These conditions indicate the emergence of an ornamental condition in the contemporary world, which requires re-evaluation and expansion of the phenomenological and experiential possibilities for architecture. If one recognizes this ornamental condition in current architecture, it is necessary to define its agenda, that is, its foundations and prerogatives; and how its system is structured: what methodologies, which processes, what kind of modes of presentation? The theory and categories of this condition can only be built with a certain methodological rigor that is preceded by an unveiling of its origins. Therefore, a genealogical treatment will be given in the first part of this thesis and plans to establish connections from the ornamental practices of the late nineteenth century up to the beginning of postmodernity, to see if there is a more dense body, with an agenda and operating systems that may have influenced the current ornamental condition of recente architecture